PLA-Based Electrospun Nanofibrous Mats Towards Application as Antibiotic Carriers: Processing Parameters, Fabrication and Characterization - Evi Christodoulou; Anastasia Chondromatidou; Nikolaos D. Bikiaris; Evangelia Balla; Marilena Vlachou; Panagiotis Barmpalexis; Dimitrios N. Bikiaris (Pharmaceutics)
Background/Objectives: Polymeric nanofibers are promising platforms for skin treatment applications due to their large surface area and high porosity, which promote enhanced drug delivery. This study aimed to develop and compare poly(lactic acid)-based (PLA) nanofibrous mats, using linear PLA and a star-like PLA-pentaerythritol (PLA-PE) copolymer, as carriers for transdermal delivery of the antibacterial agent levofloxacin (LEV). Methods: Electrospinning was employed to fabricate nanofibers from PLA and PLA-PE solutions. Spinning parameters and polymer concentrations (10% w/v PLA and 20% w/v PLA-PE) were optimized to produce uniform fibers. LEV was loaded at 10% and 20% w/w. A sum of complementary characterization techniques, including scanning electron microscopy (SEM), infrared spectroscopy (FTIR), X-ray diffraction (XRD), and differential scanning calorimetry (DSC), were applied to comparatively investigate the fibers’ morphology, structural properties, and crystallinity. Drug loading, porosity, degradation, and in vitro release profiles were evaluated. Results: PLA-PE nanofibers demonstrated smaller diameters and higher porosity (up to 90.1%) compared to PLA (82.4%), leading to enhanced drug loading (up to 34.78%) and faster degradation (55% vs. 43% mass loss over 60 days). Drug release exhibited a biphasic profile with an initial burst followed by sustained release. PLA-PE formulations released up to 60.2% LEV, compared to 38.1% for PLA counterparts. Conclusions: The star-like PLA-PE copolymer enhances nanofiber properties relevant to the desired application, including porosity, degradation rate, and drug release. These findings suggest that PLA-PE is a promising material for developing advanced transdermal antibiotic delivery systems.